HUBUNGAN ANTARA PENAMPILAN MAKANAN DENGAN SISA MAKANSIANG PADA KARYAWAN DI RUMAH SAKIT PKU MUHAMMADIYAHSURAKARTA - TRIA MAULIDA SANATH, AZMIA; , Luluk Ria Rakhma, S.Gz., M.Gizi; , Nur Lathifah Mardiyati, S.Gz., M.S (2015)
Background : Plate waste is persentation of consumed food from the total food that is served. This plate waste is influenced by some factors including the food appearance of food when it is served and the taste of food. The appearance of food include colour, shape, texture, portion, and the way it is served. The appearance of food affects the appetite of consumers. Objective : The objective of this research was to understand the correlation between the appearance of food and the plate waste especially for lunch, among staff of PKU Muhammadiyah Hospital of Surakarta. Research Method : This research was an observational study with the cross-sectional study design. The subjects of this research were 80 staff of PKU Muhammadiyah Hospital of Surakarta who got lunch from Muntahana Catering. The instruments of this research were questionnaires on the appearance of the food and Comstock for plate waste that is observed three times during lunch. Statistical test used Spearman Rank test. Result : There were 55 respondent (68,8%) who found the food was appealing enough and while the rest found it not appealing. There were 63 respondents (78%), 56 respondents (70%), 54 respondents (67,5%), 65 respondents (81,3%) who had waste of rice, animal-source side-dish, plant-source side-dish, and vegetables, respectively. The correlation tests showed P value of 0,121 for rice, 0,432 for animal-source side-dish, 0,773 for plant-source side-dish, and 0,248 for vegetables. Conclucion : There was no correlation between the appearance of food and the plate waste especially for lunch, among the staff in PKU Muhammadiyah Hospital of Surakarta. Keywords : appearance of food, plate waste, staff, food service. Bibilography : 29 : 1990 - 2013